Development of Curriculum Developmental Model in Education Sandbox to Enhance Essential Competencies for Basic Education Level Students - Keeratichamroen, Wasana; Phonnong, Isara (Ratchaphruek Journal, 2023)
In the 21st century, the curriculum for all levels of education will be competency-based, with a focus on developing students’ necessary knowledge, skills, and attitudes for their future lives. The objectives of this research were to: 1) Develop a curriculum developmental model in Education Sandbox; and 2) Examine the outcomes of implementing the curriculum developmental model in Education Sandbox. The research was conducted by using the mixed methods research, consisting of two phases. Phase I involved creating the curriculum development model and included three curriculum development experts as a sample group. Phase II consisted of piloting the curriculum development model with a sample group of 25 fourth-grade students. The research tools were the scoring rubric of curriculum development model in Education Sandbox and scoring rubric of competencies. Data were analyzed by mean, standard deviation, and t-test for dependent. The findings indicated that: 1) the curriculum developmental model created for Education Sandbox which was a systematic model, and 2) teachers were able to effectively develop a curriculum following the procedures outlined in the curriculum developmental model. This curriculum had a positive impact on enhancing the students’ six types of competencies. However, it was recommended that teachers would be provided with training to acquire skills in creating digital materials on their own.